Effect of two new teat dip prepatations on teat condition, somatic cell count, and incidence of mastitis under natural exposure - Burkitt, E.L.; Miller, W.F.; Scheffel, Michael V.; Titgemeyer, Evan C.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Application of an iodophor teat dip before and after milking is a common practice in the dairy industry as an effective method of preventing mastitis by reducing microbial populations at the teat end. Overall effectiveness of a teat dip is a function of its ability to reduce the microbial population and maintain a pliable teat skin condition. The objective of this study was to evaluate a new conditioning component in iodophor teat dips containing either 0.5% or 1.0% iodine. Two experiments were conducted during late winter (133 cows) and during summer (104 cows) to evaluate two new iodophor teat dips developed by KO Manufacturing, Inc., Springfield, Mo. The two teat dips contain a nontraditional conditioning agent designed to sustain the lipid bilayer of the teat skin and improve skin condition. Dinerin (0.5% iodine) was equally effective as Westfalia-Surge Derma-Kote during the winter study in preventing new mammary infections based on the number of new clinical cases of mastitis and somatic cell counts. Teat and teat end condition were similarly maintained by both teat dips during the winter study. Two Dinerin teat dips, 0.5% and 1.0% iodine, were compared to Westfalia-Surge Teat-Kote 10-3 (0.5% iodine) during the summer. The Dinerin 0.5% iodine dip was most effective in preventing new cases of clinical mastitis. Teat and teat end conditions were maintained similarly by all three dips. Somatic cell counts were similar among treatments when cows that developed clinical mastitis were deleted from the analysis. The numbers of clinical mastitis cases were 5, 0, and 6 for cows dipped with Westfalia-Surge Teat-Kote 10-3, Dinerin 0.5% iodine, and Dinerin 1.0% iodine, respectively.
Keywords: Dairy; Teat dips; Mastitis; Somatic cells